Barbiturates and valproates in the pharmacotherapy of epilepsy: clinical and psychological interactions - Natalia Tokareva (Archivos Venezolanos de Farmacología y Terapéutica, 2021)
This paper analyzes the indicators of somatization, obsessive-compulsive disorders, interpersonal sensitivity, anxiety, depression, phobic manifestations, paranoia, and psychoticism in the context of pharmacotherapy of epilepsy with barbiturates and valproates. Pharmacological therapy for epilepsy should rely on a rationally adjusted regimen with antiepileptic medicines being patient-tailored and targeted; it should have high efficiency and safety in relation to social functioning and quality of patients’ life. The research findings show that the studied group of patients with epilepsy, exposed to valproate or barbiturate therapy, is characterized by heterogeneous clinical-psychopathological and pathopsychological features. Clinico-psychopathologically, barbiturates reveal severe affective disorders and psychopathic behavior in patients with epilepsy; pathopsychological examination refers to the prominence of indicators on the scales of somatization, depression, and psychoticism, expressed in the form of somatic complaints, individual organs and systems’ disorders, and accompanied by mental equivalents, in particular on the side of the cardiovascular system, musculoskeletal system, gastrointestinal tract, etc.; depressive manifestations are also evident, reflecting the depth of affective disorders, dysphorias, suicidal tendencies, low mental activity with cognitive signs of depression, and the inclination to an avoidant, isolated lifestyle. Clinically, valproate therapy showed a predominantly neurotic character of mental changes; pathopsychological examination revealed the prevalence of obsessive-compulsive disorders, alternated with the anxiety, somatic and cognitive manifestations of anxiety.